RELATIONSHIP BETWEEN EFL PRE-SERVICE TEACHERS’ SELF-EFFICACY AND THEIR EPISTEMIC BELIEFS - Injiya, Rida Rohmata; Emaliana, Ive (English Review: Journal of English Education, 2024)
Nowadays, English is an essential language that must be mastered and has been studied for many years as a foreign language in many countries in the world. Specifically, English pre-service teachers' ability to teach students English as a foreign language requires self-efficacy and epistemic beliefs that can support students’ 21st century skills. Self-efficacy and epistemic beliefs are related to individual differences in psychological domains that can affect learning achievement. An investigation of the relationship between self-efficacy and epistemic beliefs of pre-service teachers in a reputable university in Malang, East Java was conducted in this study. This study examined the relationship between pre-service teachers' self-efficacy and epistemic beliefs. The method of this research is correlational study. A total of 85 pre-service teachers completed the self-efficacy and epistemic beliefs questionnaires. SPSS was used to analyze the questionnaire filled out by the participants and determine the results. As a result of SPSS's analysis, self-efficacy is positively correlated with epistemic beliefs, which implies a correlation in both areas. The findings of the correlation coefficient is -0.528, the correlation between self-efficacy and epistemic beliefs is negative and it means that the higher EFL self-efficacy the simpler their epistemic beliefs.  A correlation from SPSS's analysis indicates that self-efficacy and epistemic beliefs have a medium relationship.